Differential immunohistochemical expression of type I collagen and matrix metalloproteinase 2 among major salivary glands of young and geriatric mice (Journal of Applied Oral Science, 2022)
Objective: This study aimed to demonstrate the immunohistochemical changes associated with MMP-2 and type 1 collagen separately for the first time in the major salivary glands (the parotid, submaxillary, and sublingual glands) that occur with aging in mice. Material and Methods: Fourteen Balb/c white mice (50-80 g) were used in this study. The animals were divided into two equal groups. Group I consisted of young animals (2-month-old) (n=7) and Group II consisted of older animals (18-month-old) (n=7). After routine histological follow-ups, Hematoxylin-eosin (H&E), Masson’s Trichrome staining and immunohistochemical staining was performed for type I collagen and MMP-2. Results: We observed that there were age-related decreases in the number of acinar cells, increase in eosinophilic zymogen granules in cells, collagen accumulation in fibrotic areas and dilatation in interlobular ducts. Also, while type I collagen and MMP-2 immunoreactivity were moderate in the salivary glands of the young mice, they were high in the salivary glands of the old mice (p=0.001). In the H-score assessment, MMP-2 immunoreactivity was lower at a significant level in young mice than in old mice (p=0.001). Conclusions:This study showed that anatomical, physiological and morphological abnormalities occur in all three major salivary glands as a natural consequence of aging.